Impacted maxillary canine in unilateral cleft lip and palate: A literature review - Ali Alqerban (Elsevier, 2019)
Background: The incidence of canine impaction in unilateral cleft lip and palate (UCLP) is increasing and in most cases is a part of a syndrome. The provision of different treatment modalities in these patients is a challenging and daunting task. Objective: The objective of the present review was to scrutinize the available evidence on canine impaction in UCLP patients. Materials and methods: Using PRISMA guidelines, a review was conducted via the PubMed (MEDLINE), ISI Web of Knowledge, Google Scholar, and Embase databases using different keywords. Studies were shortlisted and inspected according to the following inclusion criteria: (1) papers published in English over the past 40 years, (2) study participants with maxillary canine impaction in unilateral cleft lip and palate, (3) studies reporting on canine impaction and cleft lip and palate, and (4) no age limit was applied so studies published on both children and adults with unilateral cleft lip and palate and canine impaction were included. Studies which justified inclusion criteria were included whereas the rest of the studies were removed. Results: A total of 279 studies were retrieved using the search strategy. After removing duplicate reports and scrutinizing those based on title and abstract, 54 studies were shortlisted for full text review. Following the review, 22 studies were included in the final list. The presentation of data was based on the year of study, type of cleft, gender, age of bone graft, spontaneous eruption, and surgical exposure. Conclusion: Every UCLP patient is different and treatment modalities should vary according to the characteristics, subjective response, and variability of the malformation. Keywords: Maxillary canine, Cleft lip, Cleft palate, Impaction